Poverty, human capital, life-cycle and the tax and transfer bases: The role of education for development and international competition - Hans-Georg Petersen (Universität Potsdam, Lehrstuhl Finanzwissenschaft, 2011)
The paper is based on an individual life-cycle model, which describes the purely economic components of human capital. The present value of human capital is determined by all future income flows, which at the same time constitute the individual as well as the total tax base of a nation. Therefore, the income of the productive population determines the total tax revenue, which is spent for public goods (including education) and transfers (for poverty reduction). The efficient design of the education system (by private and public education investments) determines the quality of the human capital stock as well as the future gross income flows. The costs of public goods and the transfer expenditures have to be financed from the total tax revenue, which also affects the individual tax burden via the specific tax bases and tax rates. Especially the redistribution of income is connected with serious disincentives, influencing the preferences for work and leisure as well as for consumption and saving. An efficient tax and transfer system being accompanied by an education system financed in public private partnership, which treats equally labor and capital income, sets positive incentives for the formation of human, financial, and real capital. An important prerequisite for a sustainable growth process is the efficient design of the social security system, being based on the family as well as a collective risk equalization scheme. If that system is diminishing absolute poverty in an appropriate time period by transfers and vocational education measures for the grown-up as well as high quality primary, secondary and tertiary education programs for the children, the transfer expenditure would decrease and the tax bases (income and consumption) increase, lowering the burden on the productive population. For the first time, this micro model presented in this paper pools all the relevant variables for development within a simple life-cycle model, which can also be used for a powerful analysis of the current failures in existing tax and transfer schemes and fruitful empirical investigations. Hence, an efficient tax and transfer scheme strongly contributes to an improved national position in the global competition.
urn:nbn:de:kobv:517-opus-53968
Keywords: D1; D31; D91; H21; H31; H55; I21; I22; I32; J17; J24; O15; P46; 330; poverty; human capital; life-cycle analysis; lifetime income; education; taxation; transfers; redistribution; risk equalization; social security